Testing for optic ataxia in a blind field - Khan, Aarlenne; Pisella, Laure; Delporte, Ludovic; Rode, Gilles; Rossetti, Yves (Frontiers in Human Neuroscience, 2013)
Optic ataxia is a component of Balint’s syndrome and is a disorder that results from damage to the posterior parietal cortex leading to deficits in reaching and grasping objects presented in the visual field opposite to the damaged hemisphere. It is also often the case that Balint’s syndrome is accompanied by visual field defects due to the proximity of parietal and occipital cortices and also due to the subcortical pathway relaying visual information from the retina toward the cortex passing underneath the parietal cortex. The presence of primary visual defects such as hemianopia often prevents clinicians from diagnosing higher-level visual deficits such as optic ataxia; the patient cannot reach to targets he/she cannot see. Here, we show that through the use of a paradigm that takes advantage of remapping mechanisms, we were able to observe optic ataxia in the blind field. We measured reach endpoints of a patient presenting with left optic ataxia as well as a quadrantanopia in the left lower visual field in eye-static and eye-dynamic conditions. In static conditions, we first asked the patient to reach to targets viewed in her non-optic ataxic intact right visual field (fixating on the left of the target array). In this case, the patient showed undershoots equivalent to controls. Next, we asked her to reach to (the same) targets viewed in the upper left optic ataxic but intact visual field (fixating to the right of the target array). The undershooting pattern increased greatly, consistent with unilateral left optic ataxia. In dynamic conditions, we asked her to view targets in her good (right lower) visual field before reorienting her line of sight to the opposite side, causing the internal representation of the target to be updated into the opposite (ataxic) blind visual field. The patient then reached to the remembered (and updated) location of the target. We found errors typical of optic ataxia for reaches guided toward the quadrantanopic field. This confirmed